Psychiatric sequelae of traumatic brain injury - Suprakash Chaudhury; Partha Sarathi Biswas; Subodh Kumar (Medical Journal of Dr. D.Y. Patil University, 2013)
Almost half of the people suffering traumatic brain injury (TBI) may later be diagnosed with psychiatric disorders. The literature (PubMed, IndMed of past 30 years) on psychiatric disturbances associated with TBI is reviewed. The authors highlight the close link between head injury and psychiatry and provide an overview of the epidemiology, risk-factors, and mechanisms of psychiatric sequelae including, cognitive deficits, substance abuse, psychoses, mood disorders, suicide, anxiety disorders, dissociative disorders, post-concussion syndrome, and personality changes following head injury. The various psychiatric sequelae are briefly discussed.